A method for preparing perovskite quantum dots

Through step-by-step infusion of multi-component precursors and single variable control method, mesoporous materials are pre-embedded and sintered in step, solving the stability of perovskite quantum dots under harsh conditions and achieving high environmental tolerance and controllability of mass production.

CN114621749BActive Publication Date: 2025-01-03WUXI UTMOST LIGHT TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210312434.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-28
Publication Date
2025-01-03
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

Existing perovskite quantum dot materials are difficult to maintain stability under harsh conditions such as humidity, oxygen environment, ultraviolet light, and thermal atmosphere. In addition, the difference in melting/boiling point of the precursor during the heat treatment process leads to an imbalance in the stoichiometric ratio of the product components, affecting batch volume. Controllability and uniformity of production.

Method used

The multi-component precursor step-by-step infusion and single variable control method are used to pre-embed mesoporous materials and perform step-by-step sintering to form a firm chemical bond, which improves lattice stability and environmental tolerance.

Benefits of technology

The uniform stability and high environmental tolerance of perovskite quantum dots are achieved, and the stability to harsh conditions such as water, oxygen, light, and heat is enhanced, ensuring the controllability and product uniformity of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114621749B_ABST
    Figure CN114621749B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing perovskite quantum dots, the method comprising the following steps: after mixing a first quantum dot raw material with a solvent and a template agent, adding a mesoporous material raw material for pre-embedding to obtain a pre-embedded precursor; performing a first sintering on the pre-embedded precursor to obtain a pre-embedded mesoporous material; after mixing a second quantum dot raw material with the pre-embedded mesoporous material, performing a second sintering to obtain the perovskite quantum dots. The method can be used for batch production, and the prepared perovskite quantum dots are uniform and stable, have excellent lattice stability and environmental tolerance, and have good resistance to harsh conditions such as water, oxygen, light, and heat.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of quantum dots, and relates to a perovskite quantum dot, and in particular to a method for preparing perovskite quantum dots that can be mass-produced, uniform and stable. Background Art

[0002] With the development of science and technology, quantum dot display technology has become one of the most important components of modern optoelectronic products. The popularization and development of optoelectronic products have increasingly higher requirements for material display performance, stability and environmental protection. Compared with traditional semiconductor quantum dots, lead halide perovskite quantum dots have gradually become a strong competitor in the display field in recent years due to their excellent optical properties, low synthesis cost and environmental friendliness.

[0003] However, the current lead halide perovskite quantum dot materials are difficult to maintain good stability under harsh conditions such as humidity, oxygen environment, ultraviolet light, and hot atmosphere, which greatly affects the practical application in the display field. In this regard, researchers have conducted a lot of exploration in improving the stability of quantum dots. Among them, the core-shell structure is considered to be one of the effective means to improve the stability of quantum dots. The quantum dots are isolated from the external environment by the coating layer, which can greatly improve the weather resistance and service life of the quantum dots. In particular, the quantum dots are coated with mesoporous materials, and the pre-synthesized mesoporous materials are introduced into the preparation process of perovskite quantum dots, so that the quantum dots are generated in situ in the holes of the mesoporous materials, and then the holes are closed, so that they are protected by the closed shell material from the external environment. This method has received widespread attention due to its simple synthesis process and uniform product quality. For example, CN112980430A discloses a method for preparing perovskite quantum dots using mesoporous materials, mixing perovskite precursor materials with mesoporous materials, and calcining until the pore structure collapses to obtain a stable perovskite quantum dot material in a water-oxygen environment. The document (10.1016 / j.cej.2019.122735) reported that CsPbBr3 quantum dots were heterogeneously nucleated and effectively anchored on the surface of α-ZrP by a room temperature precipitation method, thereby improving humidity stability and thermal stability. The document (10.1126 / science.abf4460) reported a method of using a traditional liquid phase sintering method to mix and calcine perovskite precursor materials and metal-organic frameworks (MOFs), and then pour them into liquid nitrogen for rapid cooling, which can be used to mass-produce lead halide perovskites, MOFs, and glass composites. Although many such methods can obtain perovskite quantum dot materials with good stability, their light and thermal stability are still far from practical applications and cannot meet market demand.

[0004] The existing technology for preparing perovskite quantum dots has the following problems: 1) The existing preparation method of injecting perovskite precursors into mesoporous materials through heat treatment. Since the melting or volatilization rates of various precursors with different melting / boiling points in the same environment are quite different, it is inevitable that the stoichiometric ratio of the quantum dot product components will be unbalanced or the product will be uneven. 2) Even if the method of impregnating the precursor is adopted, it is still difficult to avoid the stoichiometric ratio imbalance caused by the difference in the loss rate of precursor volatilization during the subsequent heat treatment. 3) The heat treatment temperature is difficult to optimize. If the temperature is too low, it will further increase the difference in the rate of injection of different precursors into the mesoporous material, making the components more unbalanced; if the temperature is too high, the porous material will collapse and block the pores when the precursor is not fully injected, making it difficult to continue to inject. At the same time, adjacent blocks are prone to adhesion, increasing the particle size and distribution range, which brings dispersion problems to subsequent applications. 4) The difference in the precursor infusion rate caused by different melting / boiling points will continue to expand with the proportional amplification of the feed, making it difficult to ensure the controllability of the reaction environment and product uniformity during mass production. 5) The quantum dots generated by immersion infusion or melting / volatilization infusion are combined with the porous material shell through coordination or physical adsorption, and the interaction force is weak, making it difficult to ensure the luminescence stability under harsh environments such as light, heat, water, and oxygen. Summary of the invention

[0005] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing perovskite quantum dots. The preparation method can be used for mass production, and the prepared perovskite quantum dots are uniform and stable, have excellent lattice stability and environmental tolerance, and have good resistance to harsh conditions such as water, oxygen, light, and heat.

[0006] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0008] After mixing the first quantum dot raw material with a solvent and a template agent, a mesoporous material raw material is added for pre-embedding to obtain a pre-embedding precursor;

[0009] Performing a first sintering on the pre-embedded precursor to obtain a pre-embedded mesoporous material;

[0010] The second quantum dot raw material is mixed with the pre-embedded mesoporous material and then subjected to a second sintering to obtain the perovskite quantum dots.

[0011] In the present invention, high melting / boiling point precursor components and low melting / boiling point components are distributed and injected into the cavity of the mesoporous material. By controlling a single variable, the problem of product stoichiometric ratio imbalance caused by the difference in injection rates of different melting / boiling point components under the same reaction environment can be effectively prevented, thereby greatly improving the controllability of the reaction environment and product uniformity in the batch production process.

[0012] In the present invention, the sintering temperature is easier to control, and only the melting / boiling point of the quantum dot raw material added later needs to be adjusted, without balancing the difference in melting / volatilization rates between high and low melting / boiling points.

[0013] In the present invention, when the mesoporous material is synthesized, condensation and crystallization are carried out along the pre-embedded components, and a strong chemical bond is formed between the pre-embedded components and the generated mesoporous material, so that the quantum dots finally generated have better lattice stability than the traditional solid-phase sintering method or impregnation method, and can greatly enhance environmental tolerance.

[0014] As a preferred technical solution of the present invention, the perovskite quantum dots are CsBX3 quantum dots, B is Pb and / or Sn, and X is any one of Cl, Br or I or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of Cl and Br, a combination of Br and I, a combination of I and Cl, or a combination of Cl, Br and I, etc.

[0015] As a preferred technical solution of the present invention, the concentration of the first quantum dot raw material is 1 to 100mmol / L, such as 5mmol / L, 10mmol / L, 15mmol / L, 20mmol / L, 25mmol / L, 30mmol / L, 40:1mmol / L, 50mmol / L, 60mmol / L, 70mmol / L, 80mmol / L or 90mmol / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 10mmol / L.

[0016] As a preferred technical solution of the present invention, the first quantum dot raw material includes any one of CsBr, KBr, PbBr2 or PbI2 or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of CsB and KBr or a combination of PbBr2 and PbI2.

[0017] Preferably, the solvent comprises water.

[0018] Preferably, the template comprises hexadecyltrimethylammonium bromide or triblock copolymer P123.

[0019] As a preferred technical solution of the present invention, the mesoporous material is added dropwise.

[0020] Preferably, the volume ratio of the added amount of the mesoporous material raw material to the solvent is 5 to 10:100, such as 5.5:100, 6:100, 6.5:100, 7:100, 7.5:100, 8:100, 8.5:100, 9:100 or 9.5:100, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] Preferably, the mesoporous material raw material includes tetraethyl orthosilicate or aluminum isopropoxide.

[0022] In the present invention, due to the different mesoporous materials finally prepared, a pH regulator, such as ammonia water or hydrochloric acid, needs to be added before the raw materials of the mesoporous material are added dropwise. The pH regulator can be mixed with the template agent, or added after the template agent is mixed with the solvent and the first quantum dot raw material. The specific selection and addition amount of the pH regulator in the preparation of the mesoporous material are conventional techniques in the art and are not specifically limited here.

[0023] In the present invention, the obtained pre-embedded precursor is washed before the first pre-sintering, and the washing end point is that the pH of the washed solution is neutral.

[0024] As a preferred technical solution of the present invention, the temperature of the first sintering is 550°C.

[0025] Preferably, the heating rate of the first sintering is 5 to 15°C / min, such as 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min or 14°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the first sintering time is 2 to 8 hours, such as 3 hours, 4 hours, 5 hours, 6 hours or 7 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] As a preferred technical solution of the present invention, the mass ratio of the second quantum dot raw material to the pre-embedded mesoporous material is 0.4 to 1.2:2, such as 0.5:2, 0.6:2, 0.7:2, 0.8:2, 0.9:2, 1.0:2 or 1.1:2, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In the present invention, the properties of the quantum dots can be regulated by controlling the amount of the second quantum dot raw material added.

[0029] Preferably, the second quantum dot raw material includes any one of CsBr, KBr, PbBr2 or PbI2, or a combination of at least two of them. The second quantum dot raw material has a boiling point and / or melting point different from that of the first quantum dot raw material. Typical but non-limiting examples of the combination include: a combination of CsBr and KBr, a combination of CsBr and PbBr2, and a combination of CsBr and PbI2.

[0030] Preferably, the second sintering temperature is 400-650°C, such as 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, 580°C, 600°C, 620°C or 640°C, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 590°C.

[0031] Preferably, the heating rate of the second sintering is 5 to 15°C / min, such as 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min or 14°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the second sintering time is 10 to 90 min, such as 20 min, 30 min, 40 min, 50 min, 60 min, 70 min or 80 min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 30 min.

[0033] As a preferred technical solution of the present invention, after the second sintering temperature, a low melting point inorganic salt and / or an amorphous eutectic filling material is further added, preferably a nitrate, more preferably potassium nitrate or aluminum nitrate.

[0034] Preferably, the second sintered product is mixed with a filling material and subjected to heat treatment.

[0035] In the present invention, the second sintering temperature can be adjusted to simultaneously achieve quantum dot generation and mesoporous material closure, or it can be divided into two steps. When the second sintering temperature is low or the sintering time is short, the pores are closed by plugging the pores with a filling material after the quantum dots are generated, and it is preferred to directly close the pores by a one-step heat treatment.

[0036] Preferably, the mass ratio of the filling material to the second sintered product is 2:2 to 3.2, such as 2:2.1, 2:2.2, 2:2.3, 2:2.4, 2:2.5, 2:2.6, 2:2.7, 2:2.8, 2:2.9, 2:3.0 or 2:3.1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the heat treatment temperature is 350-500°C, such as 360°C, 380°C, 400°C, 420°C, 450°C or 480°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the heat treatment time is 30 to 60 min, such as 35 min, 40 min, 45 min, 50 min or 55 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] As a preferred technical solution of the present invention, the method for preparing perovskite quantum dots comprises the following steps:

[0040] After mixing a first quantum dot raw material with a solvent and a template agent, wherein the concentration of the first quantum dot raw material is 1 to 100 mmol / L, a mesoporous material raw material is added dropwise, and the mixture is stirred at a rate of 300 to 600 rpm for pre-embedding for 3 to 24 hours, wherein the volume ratio of the mesoporous material added to the solvent is 5 to 10:100, to obtain a pre-embedded precursor;

[0041] Performing a first sintering on the pre-embedded precursor, wherein the first sintering temperature is 550° C., the heating rate is 5 to 15° C. / min, and the time is 2 to 8 hours to obtain a pre-embedded mesoporous material;

[0042] Mixing a second quantum dot raw material with the pre-embedded mesoporous material and then performing a second sintering, wherein the mass ratio of the second quantum dot raw material to the pre-embedded mesoporous material is 0.4-1.2:2, the second sintering temperature is 400-650° C., and the time is 30-60 min, to obtain the perovskite quantum dots;

[0043] After the second sintering temperature, a low melting point inorganic salt and / or an amorphous eutectic filler material is added;

[0044] The second sintered product is mixed with a filling material for heat treatment, the mass ratio of the filling material to the second sintered product is 2:2-3.2, the heat treatment temperature is 350-500° C., and the time is 30-60 min.

[0045] Compared with the prior art, the present invention has at least the following beneficial effects:

[0046] (1) The preparation method of perovskite quantum dots provided by the present invention greatly improves the controllability of the reaction environment and the uniformity of the products during the preparation of quantum dots by step-by-step infusion of multi-component precursors and single variable control method;

[0047] (2) The preparation method of perovskite quantum dots provided by the present invention has good universality and can realize mass-scale production of high-quality perovskite quantum dots;

[0048] (3) The quantum dots prepared by the preparation method of perovskite quantum dots provided by the present invention can form a strong chemical bond between the core and shell, which can enhance the lattice stability and environmental tolerance. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a schematic diagram of the preparation process of Example 1 of the present invention;

[0050] Figure 2 The product pictures of the perovskite quantum dots synthesized in Example 1 and Comparative Example 1 of the present invention;

[0051] Figure 3 The photoluminescence spectra of the perovskite quantum dots synthesized in Example 1 of the present invention and Comparative Example 1 are shown;

[0052] Figure 4 This is a test diagram of the dry heat environment stability of the perovskite quantum dots synthesized in Example 1 of the present invention and Comparative Example 1;

[0053] Figure 5 This is a test chart of the blue light environment stability of the perovskite quantum dots synthesized in Example 1 of the present invention and Comparative Example 1.

[0054] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims. DETAILED DESCRIPTION

[0055] To better illustrate the present invention and facilitate understanding of the technical solution of the present invention, typical but non-limiting embodiments of the present invention are as follows:

[0056] Example 1

[0057] This embodiment provides a method for preparing perovskite quantum dots, and the process is as follows: Figure 1 As shown, the preparation method comprises the following steps:

[0058] 0.8 g of CsBr was mixed with 400 mL of deionized water and 8 g of hexadecyltrimethylammonium bromide (CTAB) and stirred at 40 °C (300 rpm) until the solution became clear;

[0059] Add 42 mL of ammonia water, continue stirring for 30 min, then add 7 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 600 rpm, then drip 30 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 3 h after dripping, and obtain a pre-embedded precursor;

[0060] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 10° C. / min, and the time is 6 hours to obtain a pre-embedded mesoporous material;

[0061] 0.887 g of PbBr2 was mixed with 2 g of the pre-embedded mesoporous material and then subjected to a second sintering process. The second sintering process was performed at a temperature of 590° C., a heating rate of 10° C. / min, and a time of 30 min to obtain CsPbBr3@MCM-41 green light quantum dots.

[0062] Example 2

[0063] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0064] 0.8 g of CsBr was mixed with 400 mL of deionized water and 8 g of hexadecyltrimethylammonium bromide (CTAB) and stirred at 40 °C (300 rpm) until the solution became clear;

[0065] Add 42 mL of ammonia water, continue stirring for 30 min, then add 7 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 600 rpm, then drip 30 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 3 h after dripping, and obtain a pre-embedded precursor;

[0066] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 10° C. / min, and the time is 6 hours to obtain a pre-embedded mesoporous material;

[0067] 1.114 g of PbI2 was mixed with 2 g of the pre-embedded mesoporous material and then subjected to a second sintering process. The second sintering process was performed at a temperature of 590°C, a heating rate of 10°C / min, and a time of 30 min to obtain CsPbBr x I 3-x @MCM-41 red light quantum dots.

[0068] Example 3

[0069] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0070] 0.8 g of CsBr was mixed with 400 mL of deionized water and 8 g of hexadecyltrimethylammonium bromide (CTAB) and stirred at 40 °C (300 rpm) until the solution became clear;

[0071] Add 42 mL of ammonia water, continue stirring for 30 min, then add 7 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 600 rpm, then drip 30 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 3 h after dripping, and obtain a pre-embedded precursor;

[0072] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 10° C. / min, and the time is 6 hours to obtain a pre-embedded mesoporous material;

[0073] 0.887 g of PbBr2 and 2 g of the pre-embedded mesoporous material are mixed and then subjected to a second sintering process, wherein the second sintering process is performed at a temperature of 550° C., a heating rate of 10° C. / min, and a time of 30 min;

[0074] The second sintered product was mixed with 2g Al(NO3)3 and ground, and then heat treated at a temperature of 500°C for 30min to obtain CsPbBr3 / Al x O y @MCM-41 green light quantum dots.

[0075] Example 4

[0076] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0077] 0.8 g of CsBr was mixed with 400 mL of deionized water and 8 g of hexadecyltrimethylammonium bromide (CTAB) and stirred at 40 °C (300 rpm) until the solution became clear;

[0078] Add 42 mL of ammonia water, continue stirring for 30 min, then add 7 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 600 rpm, then drip 30 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 3 h after dripping, and obtain a pre-embedded precursor;

[0079] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 10° C. / min, and the time is 6 hours to obtain a pre-embedded mesoporous material;

[0080] 0.887 g of PbBr2 and 2 g of the pre-embedded mesoporous material are mixed and then subjected to a second sintering process, wherein the second sintering process is performed at a temperature of 550° C., a heating rate of 10° C. / min, and a time of 30 min;

[0081] The product of the second sintering was mixed with 2g of KNO3 and ground before being heat treated at a temperature of 350°C for 60min to obtain CsPbBr3 / KNO3@MCM-4 green light quantum dots.

[0082] Example 5

[0083] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0084] 0.8 g of CsBr was stirred (300 rpm) with 400 mL of deionized water, 80 mL of hydrochloric acid, and 16 g of triblock copolymer P123 at 40 °C until the solution became clear;

[0085] After increasing the stirring rate to 600 rpm, 30 ml of tetraethyl orthosilicate (TEOS) was dripped at a rate of 1 drop / second, and stirring was continued for 24 hours after the dripping was completed. Then, the mixture was crystallized at 100°C in a hydrothermal reactor for 48 hours to obtain a pre-embedded precursor.

[0086] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 10° C. / min, and the time is 6 hours to obtain a pre-embedded mesoporous material;

[0087] 0.887 g of PbBr2 was mixed with 2 g of the pre-embedded mesoporous material and then subjected to a second sintering process. The second sintering process was performed at a temperature of 650° C., a heating rate of 10° C. / min, and a time of 60 min to obtain CsPbBr3@SBA-15 green light quantum dots.

[0088] Example 6

[0089] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0090] 0.085 g of CsBr was mixed with 400 mL of deionized water and 4 g of hexadecyltrimethylammonium bromide (CTAB) and stirred at 40 °C (300 rpm) until the solution became clear;

[0091] Add 42 mL of ammonia water, continue stirring for 30 min, then add 7 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 500 rpm, then drip 20 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 5 h after dripping, and obtain a pre-embedded precursor;

[0092] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 5° C. / min, and the time is 8 h, to obtain a pre-embedded mesoporous material;

[0093] 0.400 g of PbBr2 was mixed with 2 g of the pre-embedded mesoporous material and then subjected to a second sintering process. The second sintering process was performed at a temperature of 650° C., a heating rate of 15° C. / min, and a time of 10 min to obtain CsPbBr3@MCM-41 green light quantum dots.

[0094] Example 7

[0095] This embodiment provides a method for preparing perovskite quantum dots, the preparation method comprising the following steps:

[0096] 8.512 g of CsBr was stirred (300 rpm) with 400 mL of deionized water and 20 g of hexadecyltrimethylammonium bromide (CTAB) at 40 °C until the solution became clear;

[0097] Add 42 mL of ammonia water, continue stirring for 30 min, then add 15 mL of ethyl acetate, continue stirring for 30 min, increase the stirring rate to 400 rpm, then drip 40 mL of tetraethyl orthosilicate (TEOS) at a rate of 1 drop / sec, continue stirring for 8 h after dripping, and obtain a pre-embedded precursor;

[0098] The sample is repeatedly rinsed with deionized water until the pH is neutral, and the pre-embedded precursor is subjected to a first sintering, wherein the first sintering temperature is 550° C., the heating rate is 15° C. / min, and the time is 2 h, to obtain a pre-embedded mesoporous material;

[0099] 1.200 g of PbBr2 and 2 g of the pre-embedded mesoporous material are mixed and then subjected to a second sintering process, wherein the second sintering process is performed at a temperature of 400° C., a heating rate of 5° C. / min, and a time of 90 min;

[0100] The second sintered product was mixed with 3.2 g Al(NO3)3 and ground, and then heat treated at a temperature of 450°C for 45 min to obtain CsPbBr3 / Al x O y @MCM-41 green light quantum dots.

[0101] Comparative Example 1

[0102] In this comparative example, CsBr is not mixed with the template, but is mixed with the prepared mesoporous material together with PbBr2. Other conditions are the same as those in Example 1.

[0103] Comparative Example 2

[0104] In this comparative example, CsBr is not mixed with the template, but is mixed with the prepared mesoporous material together with PbI. Other conditions are the same as those in Example 2.

[0105] Comparative Example 3

[0106] In this comparative example, CsBr is not mixed with the template, but is mixed with the prepared mesoporous material together with PbBr2. Other conditions are the same as those in Example 5.

[0107] The uniformity and weather resistance of the perovskite quantum dots prepared in Examples 1-7 and Comparative Examples 1-3 were tested, and the results are shown in Table 1 and Figure 3-5 shown.

[0108] The method of uniformity test is: visually inspect whether the color of the sample powder after heat treatment is uniform, and use a fluorescence spectrometer to test the half-peak width of the photoluminescence spectrum;

[0109] The weather resistance test method is: place the perovskite quantum dots in a dry heat environment at 85°C for 20 days and observe the change in their quantum yield; place the perovskite quantum dots in a 300mW / cm 2 After 20 days in a blue light environment, the changes in quantum yield were observed.

[0110] Table 1

[0111]

[0112]

[0113] from Figure 2 It can be seen that the sample synthesized by the pre-embedding method (right, Example 1) has a more uniform appearance color than the traditional solid-phase sintering sample (left, Comparative Example 1). Figure 3 It can be seen that the half-peak width of the pre-embedded synthetic sample (Example 1) is narrower than that of the traditional solid-phase sintered sample (Comparative Example 1), indicating that the sample size uniformity and component uniformity are better. Figure 4 It can be seen that the QY of the sample synthesized by the pre-embedding method under dry heat environment (Example 1) decreases slightly, while the QY of the sample synthesized by the traditional solid phase sintering method (Comparative Example 1) decreases significantly; Figure 5 It can be seen that the QY of the sample synthesized by the pre-embedding method (Example 1) has almost no decrease in the blue light environment, and the QY of the traditional solid-phase sintering sample (Comparative Example 1) has a slight decrease. Therefore, the weather resistance of the sample synthesized by the pre-embedding method (Example 1) is better.

[0114] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0115] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0116] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0117] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing perovskite quantum dots, characterized in that: The preparation method comprises the following steps: After mixing the first quantum dot raw material with a solvent and a template agent, a mesoporous material raw material is added for pre-embedding to obtain a pre-embedding precursor; The first quantum dot raw material is CsBr; Performing a first sintering on the pre-embedded precursor to obtain a pre-embedded mesoporous material; Mixing a second quantum dot raw material with the pre-embedded mesoporous material and performing a second sintering to obtain the perovskite quantum dots; The second quantum dot raw material is PbBr2 and / or PbI2.

2. The preparation method according to claim 1, characterized in that: The perovskite quantum dots are CsBX3 quantum dots, B is Pb and / or Sn, and X is any one of Cl, Br or I or a combination of at least two of them.

3. The preparation method according to claim 1, characterized in that: The concentration of the first quantum dot raw material is 1-100 mmol / L.

4. The preparation method according to claim 3, characterized in that: The concentration of the first quantum dot raw material is 10 mmol / L.

5. The preparation method according to claim 1, characterized in that: The solvent includes water.

6. The preparation method according to claim 1, characterized in that: The template agent includes hexadecyltrimethylammonium bromide or triblock copolymer P123.

7. The preparation method according to claim 1, characterized in that: The pre-embedding is performed under stirring, and the stirring rate is 300-600 rpm.

8. The preparation method according to claim 1, characterized in that: The pre-embedding time is 3 to 24 hours.

9. The preparation method according to claim 1, characterized in that: The temperature of the first sintering is 550°C.

10. The preparation method according to claim 1, characterized in that: The heating rate of the first sintering is 5-15°C / min.

11. The preparation method according to claim 1, characterized in that: The first sintering time is 2 to 8 hours.

12. The preparation method according to claim 1, characterized in that: The mass ratio of the second quantum dot raw material to the pre-embedded mesoporous material is 0.4-1.2:

2.

13. The preparation method according to claim 1, characterized in that: The second sintering temperature is 400-650°C.

14. The preparation method according to claim 13, characterized in that: The second sintering temperature is 590°C.

15. The preparation method according to claim 1, characterized in that: The heating rate of the second sintering is 5-15°C / min.

16. The preparation method according to claim 1, characterized in that: The second sintering time is 10 to 90 minutes.

17. The preparation method according to claim 1, characterized in that: The second sintering time is 30 minutes.

18. The preparation method according to claim 1, characterized in that: After the temperature is raised to the second sintering temperature, a low melting point inorganic salt and / or an amorphous eutectic filler material is added.

19. The preparation method according to claim 18, characterized in that: The low melting point inorganic salt and / or amorphous eutectic filling material is nitrate.

20. The preparation method according to claim 19, characterized in that: The low melting point inorganic salt and / or amorphous eutectic filling material is potassium nitrate or aluminum nitrate.

21. The preparation method according to claim 18, characterized in that: The second sintered product is mixed with a filler material and subjected to heat treatment.

22. The preparation method according to claim 21, characterized in that: The mass ratio of the filling material to the second sintered product is 2:2 to 3.

2.

23. The preparation method according to claim 21, characterized in that: The temperature of the heat treatment is 350-500°C.

24. The preparation method according to claim 21, characterized in that: The heat treatment time is 30 to 60 minutes.

25. The preparation method according to any one of claims 1 to 24, characterized in that: The preparation method comprises the following steps: After mixing a first quantum dot raw material with a solvent and a template agent, wherein the concentration of the first quantum dot raw material is 1 to 100 mmol / L, a mesoporous material raw material is added dropwise, and the mixture is stirred at a rate of 300 to 600 rpm for pre-embedding for 3 to 24 hours, wherein the volume ratio of the mesoporous material raw material to the solvent is 5 to 10:100, to obtain a pre-embedding precursor; Performing a first sintering on the pre-embedded precursor, wherein the first sintering temperature is 550° C., the heating rate is 5 to 15° C. / min, and the time is 2 to 8 hours to obtain a pre-embedded mesoporous material; Mixing a second quantum dot raw material with the pre-embedded mesoporous material and then performing a second sintering, wherein the mass ratio of the second quantum dot raw material to the pre-embedded mesoporous material is 0.4-1.2:2, the second sintering temperature is 400-650° C., and the time is 30-60 min, to obtain the perovskite quantum dots; After the second sintering temperature, a low melting point inorganic salt and / or an amorphous eutectic filler material is added; The second sintered product is mixed with a filling material for heat treatment, the mass ratio of the filling material to the second sintered product is 2:2-3.2, the heat treatment temperature is 350-500° C., and the time is 30-60 min.

26. A use of perovskite quantum dots, characterized in that: The use includes using the perovskite quantum dots prepared by the preparation method according to any one of claims 1 to 25 in optoelectronic products.

Citation Information

Patent Citations

  • Water-oxygen stable perovskite quantum dot and preparation method and application thereof

    CN112980430A

  • Cesium lead halide perovskite quantum dots and preparation method thereof

    CN113501540A

  • Perovskite quantum dot for enhancing core-shell anchoring, preparation method and application

    CN114196393A